2018
DOI: 10.1002/suco.201700051
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and property evolution of interfacial microregion of magnesium phosphate cement on mortar under various environments

Abstract: Portland cement specimens repaired with magnesium phosphate cement were soaked in Ca(OH)2 and Na2SO4 solutions for an extended period to test the bonding strength of the specimens. After the immersion, the fracture positions and surfaces of the specimens were observed and analyzed. Subsequently, the interfacial microregion of the specimens in different immersion periods was analyzed using an optical microscope and SEM. Besides, the microstructure and property evolution of the interfacial microregion of magnesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The repaired structure can deform synergistically under external loads to maintain the integrity of the structure. MPC repair materials have been widely used in many fields such as housing, bridge and road maintenance [ [13] , [14] , [15] ], but has not been widely used in the track field. Several researchers have studied the feasibility of using MPC to maintain track structures.…”
Section: Introductionmentioning
confidence: 99%
“…The repaired structure can deform synergistically under external loads to maintain the integrity of the structure. MPC repair materials have been widely used in many fields such as housing, bridge and road maintenance [ [13] , [14] , [15] ], but has not been widely used in the track field. Several researchers have studied the feasibility of using MPC to maintain track structures.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 Recently research shown that the cement strength class is one of the important parameters influencing the compressive strength of cement mortar and their results indicate that the type of cement strength class causes substantial effect on the mechanical properties of the cement mortar. 24,25 Normally scanning electron microscope (SEM) used as a powerful tool in the analysis of mortar to better identifying the effect of these parameters on physical and mechanical properties of mortar 26,27 which may help how the cement strength class and mortar components can effect on the microstructure of mortars. As mentioned above researchers have been studying the effect of W/C, S/C and cement strength class but none of them simultaneously examined the parameters of cement strength class and S/C ratio as a formula on the compressive and flexural strength of mortar.Discussion on this paper must be submitted within two months of the print publication.…”
mentioning
confidence: 99%